Raspberry Pi IoT Projects Prototyping Experiments for Makers - Shovic, John C. (Apress : Imprint: Apress, 2016)
This book is designed for entry-through-intermediate-level device designers who want to build their own Internet of Things (IoT) projects for prototyping and proof-of-concept purposes. Expert makers may also find interesting new approaches. Raspberry Pi IoT Projects contains the tools needed to build a prototype of your design, sense the environment, communicate with the Internet (over the Internet and Machine to Machine communications) and display the results. Several IoT projects and designs are shown from the start to the finish including an IoT Heartbeat Monitor, an IoT Swarm, IoT Solar Powered Weather Station, an IoT iBeacon Application and a RFID (Radio Frequency Identification) IoT Inventory Tracking System. The software is presented as reusable libraries, primarily in Python and C with full source code available. Raspberry Pi IoT Projects: Prototyping Experiments for Makers is also a valuable learning resource for classrooms and learning labs.